(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Learning a second language has become an essential part of global education, yet it continues to face many challenges. One of the major problems is the lack of exposure to the target language environment. Differences in pronunciation, grammar, and cultural background also make the process more difficult for learners. Another issue is the limited availability of qualified teachers and effective teaching materials. Moreover, motivation and learning strategies vary from student to student, affecting their overall progress. To overcome these global challenges, modern teaching methods, technology integration, and cross-cultural interaction are becoming increasingly important.